Perancangan Ulang Gedung Departemen Hasil Hutan Ipb Dramaga Dengan Pendekatan Green Design Pada Interior Dan Material - Zidni Isnani, Aisyah; Laksitarini, Niken; Faza Surya Rusyda, Hana (eProceedings of Art & Design, 2024)
Indonesia is increasingly focused on efforts to reduce global warming, with strategies that emphasize sustainable development approaches that consider environmental impacts. Bogor Agricultural University (IPB) has implemented this measure through its Green Campus initiative, in accordance with Rector Decree No. 205/It3/Lk/2015, which is in line with UI's GreenMetric ranking system. This system assesses universities' commitment to environmental sustainability through indicators such as green infrastructure, energy management, and sustainability-related education. IPB's Department of Forest Products (DHH) building, which has been in operation since 1969, faced the challenge of outdated facilities that did not meet the standards of a flagship campus. As a solution, green design was applied to the materials on the 1st Floor of the DHH Building, referring to the Material Resource and Cycle (MRC) indicator of the Green Building Council Indonesia (GBCI) Greenship Interior Space Version 1.0. The use of environmentally friendly materials aims to improve energy efficiency and comfort, as well as meet Green Campus standards in providing healthy and comfortable educational facilities. Keywords: eco-friendly, campus building, materials